The Effect of Profitability, Liquidity, and Leverage on Tax Agresiveness with Corporate Governance as Moderating Variable - Dianawati, Dianawati; Agustina, Linda (Accounting Analysis Journal, 2020)
The purpose of this study is to analyze the effect of corporate governance in moderating the relationship between profitability, liquidity, and leverage on tax aggressiveness. The study population includes financial companies listed in the Corporate Governance Perception Index (CGPI) for the 2015-2017 periods as many as 60 companies. This study used purposive sampling technique and obtained 48 companies with 35 units of analysis after reducing 13 outlier data. Data collection techniques are documentation and data analysis using descriptive statistical and inferential statistical analysis. Hypothesis testing uses the absolute difference test. The results showed that corporate governance moderates the effect of liquidity on tax aggressiveness. However, corporate governance does not moderate the relationship between profitability and leverage on tax aggressiveness. Meanwhile, profitability, liquidity, and leverage do not affect tax aggressiveness. The conclusion of the research shows the role of corporate governance in moderating the relationship between liquidity and corporate tax aggressiveness. Research findings prove the important role of corporate governance in suppressing tax aggressiveness. Properly organized corporate governance can increase transparency in corporate management to achieve company goals and reduce aggressive tax actions. Keywords: Tax Aggressiveness, Profitability, Liquidity, Leverage, Corporate Governance